Performance and Posthumanism
XXI, 352 p. 26 illus., 19 illus. in color.
Keywords: Recent technological and scientific developments have demonstrated a condition that has already long been upon us. We have entered a posthuman era, an assertion shared by an increasing number of thinkers such as N. Katherine Hayles, Rosi Braidotti, Donna Haraway, Bruno Latour, Richard Grusin, and Bernard Stiegler. The performing arts have reacted to these developments by increasingly opening up their traditionally ‘human’ domain to non-human others. Both philosophy and performing arts thus question what it means to be human from a posthumanist point of view and how the agency of non-humans – be they technology, objects, animals, or other forms of being – ‘works’ on both an ontological and performative level. The contributions in this volume brings together scholars, dramaturgs, and artists, uniting their reflections on the consequences of the posthuman condition for creative practices, spectatorship, and knowledge.